Degradation of Alizarin Yellow R Using Ultraviolet/Hydrogen Peroxide (UV/H202) Advanced Oxidation Process - Narayanasamy, Lavanyah (Universiti Teknologi PETRONAS, 2012)
The homogeneous advanced oxidation process of Ultraviolet (UV) radiation in presence of Hydrogen Peroxide (H2O2) was utilized to degrade Alizarin Yellow R, one of the most used azo dyes in the textile industry. The UV/H2O2 oxidation process is a feasible and efficient alternative for wastewater treatment from recalcitrant compounds such as azo dyes. In this study, the effects ofinitial hydrogen peroxide concentration, imtial dye concentration, initial pH and temperature were examined to determine the optimum operating conditions that give the maximum rate of degradation. Complete decolourization was achieved in the relatively short time of 60-80 minutes of irradiation. The degradation efficiency increased with increasing initial concentration of H2O2 up to an optimum value. Faster decolourization was achieved at medium acidic and neutral pH environment ranging from p 5-7 and at high temperature. The degradation reaction was found to follow the first order kinetics with respect to the dye concentration. The Box-Behnken response surface methodology (RSM) was utilized for mathematical modelling for degradation rate and used to optimize the operating condition of this degradation process. The optimum operating conditions were imtial H2O2 concentration of0.25M, initial pH of 4.59 and temperature of 50°C. Under such conditions, the proposed model of Box- Behnken fitted very well with the experimental data with R =0.989. In general, the result indicates that the UV/H2O2 technology proved to have good potential for removing dyestuff from wastewater but further treatment might be necessary to achieve complete mineralization ofthe organic intermediates.